1996
DOI: 10.1103/physrevlett.77.5090
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction and Thermal Stability of the Cubic SiC (001) Surfaces

Abstract: The (001) surfaces of cubic SiC were investigated with ab-initio molecular dynamics simulations. We show that C-terminated surfaces can have different c(2×2) and p(2×1) reconstructions, depending on preparation conditions and thermal treatment, and we suggest experimental probes to identify the various reconstructed geometries. Furthermore we show that Si-terminated surfaces exhibit a p(2×1) reconstruction at T = 0, whereas above room temperature they oscillate between a dimer row and an ideal geometry below 5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 23 publications
6
51
3
Order By: Relevance
“…The ϾCvCϽ dimer geometry on the C-SiC surface ͑001͒ is predicted to be symmetric by the CASSCF calculation, in qualitative agreement with the previous DFT calculations. 23,26,29 Symmetric dimers are also predicted on the diamond ͑001͒ surfaces by theoretical studies. 44,45 The NOON of the C-SiC ͑001͒ dimer orbital is slightly larger ͑i.e., smaller diradical character, stronger bond͒ than that on diamond ͑001͒.…”
Section: B Carbon-terminated Sic "001…mentioning
confidence: 84%
See 2 more Smart Citations
“…The ϾCvCϽ dimer geometry on the C-SiC surface ͑001͒ is predicted to be symmetric by the CASSCF calculation, in qualitative agreement with the previous DFT calculations. 23,26,29 Symmetric dimers are also predicted on the diamond ͑001͒ surfaces by theoretical studies. 44,45 The NOON of the C-SiC ͑001͒ dimer orbital is slightly larger ͑i.e., smaller diradical character, stronger bond͒ than that on diamond ͑001͒.…”
Section: B Carbon-terminated Sic "001…mentioning
confidence: 84%
“…This is different from the partially doublebonded 2ϫ1 dimer row on the diamond ͑001͒ surface. [43][44][45] Previous semiempirical, 19 LDA, 22 and GGA 20,24,26,29,32 calculations indicated that the bridging dimer is more stable than the staggered ϾCvCϽ dimer ͓Fig. 1͑c͔͒ on the C-SiC ͑001͒ 2ϫ2 surface, although the difference in energy between the two alternative reconstructions is small.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our choice is the (001) Si-terminated surface of the zincblende semiconductor SiC, which has been the subject of recent theoretical work [9,10]. The actual structure is 2×1 reconstructed, but even the ideal (truncated bulk) one is insulating, and fits well our purpose of dealing with a test case as simple as possible: the sum rule for this case takes precisely the form of Eq.…”
Section: Preprint Sissa/14/97/cm/scmentioning
confidence: 97%
“…For both sets of calculations, the use of symmetric supercells is mandatory in order to avoid spurious charge transfer and electric fields [12].…”
Section: Technique and Numerical Detailsmentioning
confidence: 99%